The Impact Evaluation of the Authority Delegation from the District Mayor to the Department of Investment and One-Stop Service (OSS) on Economic Performance in Indonesia - Tini Partini Nuryawani (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2021)
This paper examines the impact of authority delegations, both licence and non-licence, from the district mayor to the Department of Investment and One-Stop Service (OSS) in the local government on Indonesia's economic performance. This authority delegation may simplify the regulation in doing business in Indonesia and create a more favorable business environment required to promote economic performance. However, this paper finds that the authority delegation has no significant impact on economic performance. A plausible underlying argument is that there are some constraints in the implementation, such as a lack of skilled personnel and weak internal governance, which impede the efforts to simplify the business regulation setting. Also, in terms of the cultural aspect, there are risk aversion behavior and a flawed perspective on entrepreneurial activities in Indonesian society, which may flourish the informal sectors with low productivity and technology, hampering the effectiveness of such reform in boosting economic performance.